Extremal Solutions to Periodic Boundary Value Problem of Nabla Integrodifferential Equation of Volterra Type on Time Scales - Yunlong Shi; Junfang Zhao (Discrete Dynamics in Nature and Society)
We firstly establish some new theorems on time scales, and then, by employing them together with a new comparison result and the monotone iterative technique, we show the existence of extremal solutions to the following nabla integrodifferential periodic boundary value problem: u∇(t)=f(t,u,∫0t‍g(t,s)∇s),  t∈[0,a]T,  u(0)=u(ρ(a)), where T is a time scale.